The Moderating Role of Fintech Self-Efficacy in the Relationship Between Islamic Mobile Banking Usage and Islamic Investment Intention - Yulfis Wandi; Cika Maylani; Isnaini Nuzula Agustin (FEBI IAIN Langsa, 2026)
Although Islamic Financial Literacy and Religiosity are important determinants of investment behavior, limited studies have integrated these factors with fintech-related psychological constructs among Islamic mobile banking users. This study examines the effects of Islamic Financial Literacy and Religiosity on Islamic Investment Intention, with Attitude as a mediating variable and Fintech Self-Efficacy as a moderating variable, using an extended Theory of Planned Behavior (TPB) framework. A quantitative causal approach was employed using data from 366 Islamic mobile banking users in Batam. Data were collected through an online survey and analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS). The results show that Islamic Financial Literacy and Religiosity positively affect Attitude. Attitude positively influences Islamic Investment Intention and mediates the relationships between Islamic Financial Literacy, Religiosity, and Investment Intention. Fintech Self-Efficacy also has a positive direct effect on Investment Intention. However, its moderating effect on the relationship between Attitude and Investment Intention is negative and significant, indicating that users with higher technological confidence tend to make more selective investment decisions. The novelty of this study lies in integrating Islamic Financial Literacy, Religiosity, Attitude, and Fintech Self-Efficacy into a single model of Islamic investment behavior. The findings extend TPB by demonstrating the dual role of Fintech Self-Efficacy as a direct predictor and moderating factor of investment intention. Practically, the study highlights the importance of strengthening Islamic financial literacy and enhancing digital financial services to encourage participation in Islamic investment products.